Maternal and neonatal complications after IVF/ICSI-fresh embryo transfer in low-prognosis women under the POSEIDON criteria: a retrospective cohort study - Shiguang Li; Huifang Tan; Huimin Fu; Juan Du; Peihao Liu; Yingying Qin (BMC, 2023)
Abstract Background Several studies on pregnancy complications of poor ovarian response (POR) patients did not draw a consistent conclusion. The POSEIDON criteria introduces the concept of "low prognosis" and divides POR patients into four groups based on age, AFC and AMH for individualized management. We analyzed low-prognosis population and patients with regular ovarian response, compared maternal and neonatal complications and discussed the relevant risk factors. Methods A retrospective cohort study was conducted of females who achieved a singleton clinical pregnancy after IVF / ICSI-fresh embryo transfer in a single center from January 2014 to March 2019. Participants with low prognosis, as defined by the POSEIDON criteria, were enrolled in the study groups. The controls were defined as AFC ≥ five and number of retrieved oocytes > nine. Maternal and neonatal complications were compared among those groups. Results There were 2554 cycles in POSEIDON group 1, 971 in POSEIDON group 2, 141 in POSEIDON group 3, 142 in POSEIDON group 4, and 3820 in Control. Univariate analysis roughly showed that Groups 2 and 4 had an increased tendency of pregnancy complications. Multi-variable generalized estimating equations (GEE) analysis showed that the risks of GDM, total pregnancy loss, and first-trimester pregnancy loss in Groups 2 and 4 were significantly higher than in Control. The risk of hypertensive disorders of pregnancy (HDP) in Groups 2 and 3 increased, and Group 4 had an increased tendency without statistical significance. After classification by age, GEE analysis showed no significant difference in risks of all complications among groups ≥ 35 years. In patients < 35 years, the risk of HDP in POSEIDON group 3 was significantly higher than in controls (< 35 years), and there was no significant increase in the risk of other complications. Conclusion Compared to patients with regular ovarian response, low-prognosis population have increased tendency of maternal and neonatal complications. In low-prognosis patients, advanced age (≥ 35 years) might be the predominant risk factor for pregnancy complications. In those < 35 years, poor ovarian reserve could contribute to HDP.